Psychometric properties of the Valencia scale of attitudes and beliefs toward hypnosis client version (VSABH-C) in a mexican sample - Viñas Velázquez, Bertha Margarita; Mejía Ramírez, Manuel Alejandro; Mendoza, Maria Elena; Islas Limón, Julieta Yadira; Capafons, Antonio (My University, 2022)
The study analyzes the psychometric properties of the Client version of the Valencia Scale of Attitudes and Beliefs towards Hypnosis (VSABH-C), in its adaptation for Spanish speaking participants in Mexico. Reliability and validity evidence based on the internal structure is analyzed using structural equation modeling techniques in the Confirmatory Factor Analysis (CFA) modality in 1,166 Mexican university students at a state university, 139 of those students completing a re-test measure. Data replicate a previously reported model, obtaining an appropriate fit. A short 26-item version of the questionnaire is proposed, which meets the expected technical quality parameters in their psychometric properties, replicating the original eight dimensions. The internal consistency of the full scale and most of the dimensions was high. The test-retest stability was average for the full scale and for three dimensions. Results and its implications are discussed. RESUMEN El estudio analiza las propiedades psicométricas de la versión Cliente de la Escala de Actitudes y Creencias de Valencia hacia la Hipnosis (VSABH-C), en su adaptación para participantes de habla hispana en México. Se analiza la evidencia de confiabilidad y validez basada en la estructura interna utilizando técnicas de modelado de ecuaciones estructurales en la modalidad de Análisis Factorial Confirmatorio (CFA) en 1,166 estudiantes universitarios mexicanos en una universidad estatal, 139 de los cuales completaron una medida de re-test. Los datos replican un modelo reportado previamente, obteniendo un ajuste apropiado. Se propone una versión corta del cuestionario de 26 ítems, que cumple con los parámetros de calidad técnica esperados en sus propiedades psicométricas, replicando las ocho dimensiones originales. La consistencia interna de la escala completa y la mayoría de las dimensiones fue alta. La estabilidad test-retest fue media para la escala completa y para las tres dimensiones. Se discuten los resultados y sus implicaciones.
Quality & quantity
Keywords: Attitudes; Beliefs; Hypnosis; Psychometric properties; Assessment